Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Given K = (-5, -3) and M = (-1,4), find KM.

Sagot :

Let:

K = (-5, -3) = (x1,y1)

M = (-1,4) = (x2,y2)

||KM|| = √( (x2 - x1)² + (y2 - y1)² )

||KM|| = √( (-1 - (-5) )² + (4 - (-3)² )

||KM|| = √( (4)² + (7)² )

||KM|| = √(65) ≈ 8.06

We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.